Beginning learning in the home and school readiness - Arriero, Maria Lourdes V. (2006)
The family unit was chosen as the unit of investigation in this study because it consisted of multiple characteristics that influenced children development and literacy attainment. It used the qualitative method. Data was gathered from participants whose age ranges from three to four and half years old using a case study technique. Findings indicated that while early childhood development of children is average and literacy acquisition may be slow, development in preschool literacy behaviors were observed over time. Issues on home practices found to be affecting literacy development included home study environment, parental involvement, technology access, and home litearcy functions.
October 2006.
Thesis (Ph.D. Educational Psychology)--University of the Philippines, Diliman.
Keywords: Education, Preschool -- Philippines; Home and school -- Philippines; Literacy -- Philippines; Learning, Psychology of -- Philippines